Academic Writing in the Caribbean: Searching for an Identity - Milson-Whyte, Vivette Ruth (International Journal of Bahamian Studies, 2021)
Dr. Vivette Milson-Whyte gave this speech as part of the 15th Annual Anatol Rodgers Memorial Lecture Series in February 2021. The speakers were invited to give the lecture due to the fact that their edited collection Creole Composition: Academic Writing and Rhetoric in the Anglophone Caribbean received the 36th Mina P. Shaughnessy Prize from the Modern Language Association of America.